2022
DOI: 10.3389/fbioe.2021.817768
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Fractions of Spruce and Eucalyptus Lignin as a Perspective Nanoparticle-Based Platform for a Therapy Delivery in Liver Cancer

Abstract: The natural polymer, lignin, possesses unique biodegradable and biocompatible properties, making it highly attractive for the generation of nanoparticles for targeted cancer therapy. In this study, we investigated spruce and eucalyptus lignin nanoparticles (designated as S-and E-LNPs, respectively). Both LNP types were generated from high-molecular-weight (Mw) kraft lignin obtained as insoluble residues after a five-step solvent fractionation approach, which included ethyl acetate, ethanol, methanol, and aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 93 publications
1
14
0
Order By: Relevance
“…Crystal violet staining assay (CVSA) was performed as previously described ( Rudalska et al, 2014 ; Śliwka et al, 2016 ; Pylypchuk et al, 2022 ). Briefly, cells were first washed with 100 μl 1 × phosphate buffered saline (PBS) and fixed using 100 μl of 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Crystal violet staining assay (CVSA) was performed as previously described ( Rudalska et al, 2014 ; Śliwka et al, 2016 ; Pylypchuk et al, 2022 ). Briefly, cells were first washed with 100 μl 1 × phosphate buffered saline (PBS) and fixed using 100 μl of 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Cell counting kit-8 (CCK-8) assay (Sigma-Aldrich, United States) was used to determine cell proliferation and was performed using a manufacturer protocol, as recently described ( Pylypchuk et al, 2022 ). Cell proliferation was checked at two time points, 24 and 48 h post-incubation with TCM and TTM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the effect of temperature on hydroxyl content of hydroxymethylated lignin shown in this study, this trend is in line with the results of Pylypchuk et al who found that increasing the content of aliphatic hydroxyl groups of lignin can result in smaller particle sizes. [35,36] It is worth noting that as the particle size decreases the turbidity in the colloidal dispersion drops which is the result of smaller angles of light scattering (Figure 2c). SEM images confirm this trend.…”
Section: Preparation Of Hydroxymethylated Lignin Nanoparticlesmentioning
confidence: 99%